ประสิทธิผลของโปรแกรมการสร้างเสริมสุขภาพสำหรับหญิงตั้งครรภ์วัยรุ่น - อินทรางกูร ณ อยุธยา อภิรัช; ศรีพิชญาการ เกสรา; พิณตานนท์ พรรณี; เล้าวงศ์ อัญชลี; วงค์บุญยิ่ง สุภาภรณ์ (Nursing Journal CMU, 2014)
บทคัดย่อ การให้บริการสุขภาพแก่หญิงตั้งครรภ์วัยรุ่นมักใช้แนวทางเดียวกับหญิงตั้งครรภ์วัยผู้ใหญ่ซึ่งไม่สอดคล้องกับความต้องการและลักษณะของวัยรุ่น การวิจัยและพัฒนานี้มีวัตถุประสงค์เพื่อจัดทำโปรแกรมสร้างเสริมสุขภาพสำหรับหญิงตั้งครรภ์วัยรุ่น โปรแกรมประกอบด้วยการให้สุขศึกษา 3 ครั้ง เน้นการมีส่วนร่วมในการเรียนรู้และใช้สื่อที่จัดทำขึ้นประกอบด้วยภาพประกอบเสียงโดยใช้โปรแกรมคอมพิวเตอร์เพาเวอร์พอยท์แบบออโตรันจำนวน 9 ชุด ภาพพลิก หนังสือ “แม่วัยใส” สำหรับให้ข้อมูลและทำแบบฝึกหัด แผ่นพับมหัศจรรย์ลูกรักรวมทั้งมีกิจกรรมวาดภาพและเขียนเล่าเรื่อง ผู้เข้าร่วมวิจัยในกลุ่มทดลองมี 19 คน ส่วนกลุ่มควบคุมมี 10 คนผลการวิจัยพบว่ากลุ่มทดลองมีความเครียดและภาวะซึมเศร้าลดลง (p<0.05) มีคะแนนการปฏิบัติตัวในระยะตั้งครรภ์เพิ่มขึ้น (p<0.01) มีพัฒนกิจทั้ง 4 ด้านเพิ่มขึ้น คือ การยอมรับการตั้งครรภ์ สัมพันธภาพระหว่างคู่สมรสการเตรียมตัวคลอด และการยอมรับบทบาทมารดา (p<0.05) ส่วนกลุ่มควบคุมมีแหล่งสนับสนุนเพิ่มขึ้น และมีพัฒนกิจด้านการปรับตัวต่อการเปลี่ยนแปลงเพิ่มขึ้น (p<0.05) ผลลัพธ์ด้านสูติศาสตร์และความพึงพอใจต่อบริการสุขภาพระหว่างกลุ่มทดลองและกลุ่มควบคุมไม่แตกต่างกัน (p>0.05) กลุ่มทดลองมีคะแนนความพึงพอใจต่อกิจกรรมหรือสื่อที่จัดให้เฉพาะกลุ่มทดลองเท่ากับ 3.4/4.0 (S.D.=0.5) ข้อเสนอแนะ คือควรมีการนำโปรแกรมและสื่อที่จัดทำขึ้นไปใช้อย่างต่อเนื่องต่อไป โดยมีการเพิ่มกิจกรรมการสร้างเสริมคุณค่าในตนเอง คำสำคัญ: โปรแกรม สุขภาพทางจิตสังคม การปฏิบัติตัว พัฒนกิจของหญิงตั้งครรภ์ หญิงตั้งครรภ์วัยรุ่น Abstract Health care for pregnant adolescents has been practically provided in a similar conditionto that for pregnant adults, which is not in accordance with adolescents’ needs and nature.The research and development project aimed to develop a promoting program for pregnantadolescents. The program consisted of 3 heath education sessions focusing on participatinglearning. Teaching materials were also developed, including 9 sets of pictures and sound usingan auto - run PowerPoint computer program, flipcharts, a Mae-wai-sai booklet containinginformation and exercises, and a child miracle leaflet. Activities related to drawing and writingstories were included. There were 19 subjects in an experimental group whereas a controlgroup consisted of 10 subjects. The results showed that the experimental group was found tobe lower in stress and depression (p<0.05), to be higher in self-care practice (p<0.01) andhigher in 4 subscales of pregnancy developmental tasks: pregnancy acceptance, spousalrelationship, childbirth preparation, and maternal role acceptance (p<0.05). The control groupwas found to be higher in support and a pregnancy developmental task subscale of adaptationto changes (p<0.05). Obstetric outcomes and service satisfaction were not different betweenthe experiment and the control groups (p>0.05). The mean score of satisfaction with programactivities and materials was 3.4/4.0 (S.D.=0.5). It is recommended that the developed programand materials should be implemented continuously. Additionally self-esteem promoting shouldbe added to the program. Key words: Program, Psychosocial Health, Self-Care Practice, Pregnancy Developmental Tasks,Pregnant Adolescents